2017
DOI: 10.1186/s12863-017-0545-z
|View full text |Cite
|
Sign up to set email alerts
|

A major QTL on chromosome 7HS controls the response of barley seedling to salt stress in the Nure × Tremois population

Abstract: BackgroundSeedling establishment is a crucial and vulnerable stage in the crop life cycle which determines further plant growth. While many studies are available on salt tolerance at the vegetative stage, the mechanisms and genetic bases of salt tolerance during seedling establishment have been poorly investigated. Here, a novel and accurate phenotyping protocol was applied to characterize the response of seedlings to salt stress in two barley cultivars (Nure and Tremois) and their double-haploid population.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 90 publications
2
19
0
Order By: Relevance
“…In contrast, there was no significant contribution of genotype in RL-Control, but it increased gradually (from 11% to 22%) with increasing salinity up to 240 mM NaCl (Table S3). This indicated a strong genetic effect on root growth under moderate salt stress, as had already been demonstrated by the discovery of major QTLs in the OWB barley population (Witzel et al 2010) and NT barley population (Xue et al 2017). Hence, our results suggest that potential genetic influence on barley seedling traits is organ-(shoot vs. root) and condition-dependent.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In contrast, there was no significant contribution of genotype in RL-Control, but it increased gradually (from 11% to 22%) with increasing salinity up to 240 mM NaCl (Table S3). This indicated a strong genetic effect on root growth under moderate salt stress, as had already been demonstrated by the discovery of major QTLs in the OWB barley population (Witzel et al 2010) and NT barley population (Xue et al 2017). Hence, our results suggest that potential genetic influence on barley seedling traits is organ-(shoot vs. root) and condition-dependent.…”
Section: Discussionsupporting
confidence: 85%
“…A vertical seedling growth system, which has been described by Xue et al (2017), was used to germinate the collected seeds in 80, 160, 240, 320 and 400 mM sodium chloride (NaCl) solution, in parallel with control condition (no salt added). All "seeds" (referring in the wide sense to the barley grain spikelet) were incubated for 7 days in a growth chamber at 20 °C without light.…”
Section: Phenotyping Seedling Traits Under Different Salinitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Under experimental conditions aimed at studying seed germination or seedling growth, saline conditions and the osmotic component of drought stress are frequently simulated by sodium chloride (NaCl) and polyethylene glycol (PEG), respectively (Abdel-Ghani et al 2015;Shi et al 2015). To date, two major QTL controlling the response of barley seedlings to salt stress have been identified on chromosome 5HL in the Oregon Wolfe Barley (OWB) mapping population (Witzel et al 2010), and on chromosome 7HS in a Nure × Tremois (NT) population (Xue et al 2017). In contrast, only minor QTL were detected when seedlings of the OWB population were exposed to osmotic stress (Bálint et al 2008), and similar results were observed for other recombinant populations (Wójcik-Jagła et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The mathematical Sigmoid model has also been applied to depict the dynamic response of seminal root growth in maize seedlings exposed to different salinities (Khan et al 2003). Similarly, the Hill function of the Sigmoid model was employed to simulate the response of barley seedlings to salt stress, and key parameters from the simulation curves (e.g., maximum seedling length (L max ), salt concentrations leading to 50% reduction in L max (Salt 50 )) were extracted for QTL mapping (Xue et al 2017). To date, these methodologies have been used separately for genetic analyses; however, their combination might increase the accuracy and efficiency of QTL discovery.…”
Section: Introductionmentioning
confidence: 99%